Clinical And Immunological Characteristics of Allergic Diseases in Adolescents - Abdullaev Nurboy Chunaevich (Zien Journals, 2022)
This article contains information about allergic diseases, information about the clinic of allergic diseases in teenagers.
Keywords: allergy; diagnosis; research; prevention